Synthesis and investigation of YFeTiO5 - YFeSnO5 multicomponent system - R. H. Grigoryan (ՀՀ ԳԱԱ հրատ.)
It was firstly investigated YFeTiO5 - YFeSnO5 multi component system by x -rays methods. Samples of YFeTi1-хSnхO5 ware synthesized from oxides of appropriate metals in hydrogen - oxygen flames low temperature plasma [1] and classical ceramic technology. All synthesized samples were roasted at Т = 1170К during four hours. The X-ray diffractions of samples with equal composition synthesized by different ways are identical. Comparison powder difractograms of samples have shown structural uniformity of system YFeTiO5 - YFeSnO5, representing continuous number of firm solutions with which reach on all concentration intervals. The formed firm solutions crystallize in rhombic system of pseudo-brookite structure.
Keywords: Chemistry